2017
DOI: 10.1186/s12944-017-0608-1
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of skin function associated with obesity and specific correlation to local/systemic parameters in American women

Abstract: BackgroundObesity is considered problematic not only as a major cause of diabetes, hypertension, and dyslipidemia, but also as a risk of intractable dermatosis; however influence of obesity on skin function has not been clarified. To clarify the mechanism of obesity-associated skin disorders, we aimed to characterize the skin function of subjects with obesity, and identify possible influencing factors.MethodsComplex analyses including instrumental measurement, biochemical and lipidomics were performed for faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 36 publications
2
42
1
Order By: Relevance
“…Obesity has been associated with decreased collagen deposition and slower wound healing in animal studies 17 . Increased body weight also raises the levels of tumour necrosis factor (TNF) and interleukin‐6, which is an adipose tissue‐derived pro‐inflammatory cytokine 18 . Both cytokines have the potential to induce local skin inflammation and worsen underlying IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity has been associated with decreased collagen deposition and slower wound healing in animal studies 17 . Increased body weight also raises the levels of tumour necrosis factor (TNF) and interleukin‐6, which is an adipose tissue‐derived pro‐inflammatory cytokine 18 . Both cytokines have the potential to induce local skin inflammation and worsen underlying IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified an error. In the description in Fig.…”
Section: Correctionmentioning
confidence: 99%
“…Recent studies have shown that obesity creates variations in skin physiology 5,29,30 . These changes include but are not limited to skin barrier function, epidermal changes, dermal changes, and changes to the vascular and capillary recruitment function.…”
Section: Introductionmentioning
confidence: 99%